Structural and Biomechanical Corneal Differences between Type 2 Diabetic and Nondiabetic Patients - João N. Beato; João Esteves-Leandro; David Reis; Manuel Falcão; Vítor Rosas; Ângela Carneiro; Fernando Falcão Reis (Journal of Ophthalmology)
Purpose. To analyze and compare corneal structural and biomechanical properties, characterized by corneal hysteresis (CH) and resistance factor (CRF), between patients with and without type 2 diabetes mellitus (DM), and determine the main ocular variables that influence them. Methods. Sixty diabetic and 48 age- and sex-matched non-DM patients were enrolled in this cross-sectional study. The DM group was analyzed according to DM duration (<or ≥ 10 years), HbA1c levels (<or ≥ 7%), and presence of retinopathy. CH and CRF were evaluated using the Ocular Response Analyzer® (ORA). Central corneal thickness (CCT) was determined by Scheimpflug tomography (Pentacam® HR). Intraocular pressure was obtained with ORA (IOPcc) and Goldmann applanation tonometry (IOP-GAT). Univariate and multivariate linear regression analyses were performed to evaluate the relationship between demographical, clinical, and ocular variables with the biomechanical properties. Results. There were no statistically significant differences in the CH and the CRF between DM and non-DM groups (p=0.637 and p=0.439, respectively). Also, there was no statistical difference between groups for the CCT, IOPcc, or IOP-GAT. Multivariate linear regression analysis showed that CH was positively associated with CCT (p<0.001) and negatively associated with IOPcc (p<0.001), while CRF was positively associated with CCT (p<0.001) and IOPcc (p=0.014). Conclusion. The CCT and IOPcc were found to be the main parameters that affect corneal biomechanical properties both in diabetics and controls. In this study, there was no significant effect of DM type 2 on corneal biomechanics.